1999
DOI: 10.1046/j.1365-2958.1999.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies complementation in Saccharopolyspora erythraea : elucidation of the function of oleP1, oleG1 and oleG2 from the oleandomycin biosynthetic gene cluster of Streptomyces antibioticus and generation of new erythromycin derivatives

Abstract: SummaryTwo glycosyltransferase genes, oleG1 and oleG2, and a putative isomerase gene, oleP1, have previously been identified in the oleandomycin biosynthetic gene cluster of Streptomyces antibioticus. In order to identify which of these two glycosyltransferases encodes the desosaminyltransferase and which the oleandrosyltransferase, interspecies complementation has been carried out, using two mutant strains of Saccharopolyspora erythraea, one strain carrying an internal deletion in the eryCIII (desosaminyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
(61 reference statements)
3
48
0
1
Order By: Relevance
“…This will require the use of "flexible" glycosyltransferases, and in this context, a few examples of glycosyltransferase substrate flexibility have been reported (8,46,61). The S. antibioticus OleG2 glycosyltransferase has been shown to transfer L-oleandrose and L-olivose (this work) and also L-rhamnose (12). This "substrate flexibility" of the OleG2 glycosyltransferase opens up the possibility of using this sugar transfer enzyme as a genetic tool for further studies leading to the generation of novel glycosylated macrolides.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This will require the use of "flexible" glycosyltransferases, and in this context, a few examples of glycosyltransferase substrate flexibility have been reported (8,46,61). The S. antibioticus OleG2 glycosyltransferase has been shown to transfer L-oleandrose and L-olivose (this work) and also L-rhamnose (12). This "substrate flexibility" of the OleG2 glycosyltransferase opens up the possibility of using this sugar transfer enzyme as a genetic tool for further studies leading to the generation of novel glycosylated macrolides.…”
Section: Discussionmentioning
confidence: 87%
“…The other two glycosyltransferases are involved in the transfer of D-desosamine and L-oleandrose to the oleandolide, as was demonstrated by gene disruption (35). Recently, it has been shown that oleG1 complements an S. erythraea mutant lacking eryCIII and that oleG2, when transformed into a mutant lacking eryBV, produces a new compound that contains a rhamnosyl residue attached to the C-3 position of the erythronolide B (12). Therefore, it has been proposed that OleG1 and OleG2 act as the D-desosaminyl-and L-oleandrosyl-glycosyltransferases, respectively (12).…”
Section: 6-dehydration Activity Has Been Demonstrated In Vitro Formentioning
confidence: 98%
See 1 more Smart Citation
“…For example, expression of the gene encoding the desosaminyltransferase (OleG1) from the oleandomyicn pathway in an S. erythraea mutant lacking the endogenous desosaminyltransferase (EryCIII) restored erythromycin A (206) production, [261] establishing the proposed functions for both EryCIII and OleG1. When the gene encoding the oleandrosyltransferase OleG2 from the oleandomyicn pathway was expressed in an S. erythraea mutant Scheme 16.…”
Section: Erythromycinmentioning
confidence: 95%
“…Insertional inactivation of oleG1 produced a mutant that accumulates the macrolactone 8,8a-deoxyoleandolide, because both OleG1 and OleG2 glycosyltransferases were affected in this mutant by a polar effect (16). Complementation experiments using eryBV-and eryCIII-minus mutants of the erythromycin producer Saccharopolyspora erythraea showed that oleG1 complemented an eryCIII-minus mutant and oleG2 complemented an eryBV-minus mutant (6). Therefore, it was concluded that D-desosamine and L-oleandrose were the substrates for the OleG1 and OleG2 glycosyltransferases, respectively.…”
mentioning
confidence: 99%